OPERATING SYSTEM FOR WIRELESS SENSOR NETWORKS AND AN EXPERIMENT OF PORTING CONTIKIOS TO MSP430 MICROCONTROLLER - Thang Vu Chien; Hung Nguyen Chan; Thanh Nguyen Huu (Faculty of Computer Science - Universitas Indonesia, 2012)
Wireless Sensor Networks (WSNs) consist of a large number of sensor nodes, and are used for various applications such as building monitoring, environment control, wild-life habitat monitoring, forest fire detection, industry automation, military, security, and health-care. Each sensor node needs an operating system (OS) that can control the hardware, provide hardware abstraction to application software, and fill in the gap between applications and the underlying hardware. In this paper, researchers present OS for WSNs and an experiment of porting contikiOS to MSP430 microcontroller which is very popular in many hardware platforms for WSNs. Researchers begin by presenting the major issues for the design of OS for WSNs. Then, researchers examine some popular operating systems for WSNs including TinyOS, ContikiOS, and LiteOS. Finally, researchers present an experiment of porting ContikiOS to MSP430 microcontroller. Wireless Sensor Networks (WSNs) terdiri dari sejumlah besar sensor nodes, dan digunakan untuk berbagai aplikasi seperti pemantauan gedung, pengendalian lingkungan, pemantauan kehidupan habitat liar, deteksi kebakaran hutan, otomatisasi industri, militer, keamanan, dan kesehatan. Setiap sensor nodememerlukan sistem operasi (SO) yang dapat mengontrol hardware, menyediakan abstraksi hardware untuk aplikasi perangkat lunak, dan mengisi kesenjangan antara aplikasi dan hardware. Dalam penelitian ini, peneliti menyajikan SO untuk WSNs dan percobaan dari port contikiOS untuk MSP430 mikrokontroler yang sangat populer di platformhardware untuk WSNs. Peneliti memulai dengan menghadirkan isu utama yaitu desain SO untuk WSNs. Lalu, penelitimemeriksa beberapa sistem operasi populer untuk WSNs, termasuk TinyOS, ContikiOS, dan LiteOS. Akhirnya penelitimenyajikan sebuah percobaan dari port ContikiOS untuk MSP430 mikrokontroler.